Soil and Water Iron Microbes in North Carolina (SWIMNC) Outreach: Positive Impact of Combining Classroom and Field Experiences to Promote Learning and Shift Attitudes - Andrews, Megan Y.; Whitaker, Andrew H.; Sowers, Tyler D.; Duckworth, Owen W. (Frontiers in Education, 2020)
. Environmental science is a topic that lends itself to innovative teaching methods in secondary education. Many aspects of environmental science have macroscopically observable components, creating myriad opportunities to link classroom lessons and practical, outdoor exercises to both pique the students’ curiosity about the world around them, and reinforce the fundamental knowledge imparted through books and lectures via active learning. Linking university research teams and local science teachers is a key way to incorporate cutting edge science into the classroom and to provide students with the experience of being a “scientist for the day”. Through the Soil and Water Iron Microbes in North Carolina (SWIMNC) project, local science teachers were recruited to participate in a university outreach program to bring current biogeochemical science to both students and teachers. A team of faculty, postdoctoral research associates, and graduate students delivered a classroom presentation on the importance of metals and iron oxidizing bacteria, emphasizing the role microbes play in affecting the availability and transport of metals in the environment. The group then traveled to a nearby site where iron oxides (bright orange deposits common in shallow water) form to collect samples and other field data. Students worked in small teams with a member of the university to collect and label samples, take measurements of pH and temperature, and make and record observations. Pre- and post- activity surveys assessed the impact of the combined classroom and field event on student’s knowledge and attitudes relating to environmental science. Survey results indicate that the combination of classroom activities and hands-on field sampling and analysis had a positive influence on students’ knowledge and views of environmental science. This impact was most pronounced on middle school students, but was still significant for high school students. University outreach programs provide a clear opportunity to integrate current topics into secondary school classrooms. Here, research about how bacteria and metals interact in the environment provides an avenue to incorporate current research data and demonstrations into classroom activities, giving teachers and students the opportunity to use these approaches in lessons and projects to gain a better understanding of environmental science.